Anakinra for Treatment-Resistant Kawasaki Disease: Evidence from a Literature Review - Ferrara, Giovanna (Paediatr Drugs, 2020)
Kawasaki disease (KD) is one of the most common vasculitides of childhood and the main cause of acquired heart disease in developed countries. Intravenous immunoglobulin (IVIG) in association with aspirin represents the main treatment for KD. However, 10–20% of patients fail to respond to standard treatment and have an increased risk of cardiac complications. There is currently no accepted protocol for treatment of resistant cases. Several authors highlighted the role of interleukin-1 (IL-1) as a mediator of inflammation in KD and suggested the possibility of using IL-1 or its receptor as a target of therapy. The use of IL-1 inhibitors in patients with KD has been reported in the scientific literature, but data are largely limited to individual case reports and small case series. We summarized the scientific literature related to the use of anakinra, analyzing preclinical and clinical data. Thirty-eight patients have been described so far, most of them with KD-related complications. Twenty-two were described in case reports and case series, while 16 were patients from the completed KAWAKINRA phase IIa study. Almost all patients received clinical benefit, and no relevant side effects were noted. Based on this evidence, in our opinion, anakinra may be considered as an option after the failure of the first IVIG infusion, especially in patients with coronary involvement.